Evaluasi dan Perbaikan Proses Bisnis Menggunakan Business Process Improvement (BPI) (Studi Kasus: Bidang Mutasi, Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Batu) - Muhammad Averous Mahdafikiyah; Ismiarta Aknuranda; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The mutation division is one of the BKPSDM divisions that has main service to help realize the implementation of personnel affairs. These services include managing formation, completing promotions and submitting employee layoffs. However, there are still some problems that hinder the running of the service, such as difficulties in collecting the entire record of employee data for the preparation of formation and long processing on completion of promotions and employee dismissal. Therefore, analysis, evaluation and improvement of business processes are needed to overcome the problems and optimize the running of the business process. In this research, business process modeling is carried out using Business Process Modeling and Notation (BPMN), analyzing and evaluating each activity using Failure Mode and Effect Analysis (FMEA) and improving business processes through the Business Process Improvement (BPI) method. After that, the simulation is run between the current business process model and the recommendation to determine the validity and results of the time analysis. Based on the simulation results through Bizagi Modeler, it was found that each business process has a valid value and an increased time on business process recommendation. Business process in managing the formation there was an increase in time 12.09%, completion of promotion 53.68% and submission of employee layoffs 2.41%.